Drinking motives as mediator between social anxiety and alcohol misuse among private university students in Klang Valley - Raj, Sharivini Lekha Youva; Yasin, Mohd Azhar Mohd; Othman, Zahiruddin; Othman, Azizah (Elsevier, 2016)
As social anxiety becomes a threat, drinking becomes a trend in experiencing relaxation, acceptance of peers and decreases performance fear. Individuals with social anxiety disorder are two to three times more likely to establish alcohol use disorder. This paper sought to assist in integrating a detailed analysis of potential unique mediator of alcohol use among socially anxious people. The findings suggested that students with high social anxiety endorsed greater negative reinforcing drinking motives (coping, conformity) which independently mediate the relationship between the social anxiety and alcohol use, whereas enhancement motives and social motives were statistically non-significant.